Factors predicting smoking avoidance behaviors among high-school students - Pothimas, Nisakorn; Apirattanawong, Sangduan; Pongrangsarn, Phattharamanat; Petcharat, Manika (Thai Journal of Nursing, 2021)
This cross-sectional study aims to examine predicting factors on smoking avoidance behavior among high-school students. Participants were 148 high-school students attending the 30th Thailand National Science Week, Naresuan University with voluntarily recruitment. Data collection was performed by using self-administered questionnaires. Descriptive statistics and ordinal logistic regression analysis were employed for data analysis. Results reveal that majority of the participants are female (57.4%) with the average age of 16.68 years old. Seven point four percent of the participants have had experience of tobacco smoking. The average age of the first smoking is 14.27 years old and the reason for their first smoking is to try once. Predictive factors of smoking avoidance behavior among high-school students include attitude towards smoking avoidance behavior at the moderate level (OR = -1.17, 95 % CI = -2.064 to -0.275), parents’ supervision at the low level (OR = -3.64, 95 % CI = -5.495 to -1.776) and at the moderate level (OR = -1.27, 95 % CI = -2.158 to -0.372), and social regulations at the low level (OR = -1.20, 95 % CI = -2.335 to -0.065) with overall prediction power of 48.7 percent at p < .05.